Improvements in mood symptoms, cognitive symptoms and functioning in outpatients with mdd in greece treated with vortioxetine: A patient-rated evaluation. (13th April 2021) - Galanopoulos, A.; Tsiolka, E.; Ntounas, P.; Mpelimpasakis, D.; Karakoutas, D.; Sidiropoulos, N.; Mpougiouklis, I.; Kyziridis, K.; Papalexi, E.
Abstract : Introduction: Functional recovery is the contemporary treatment goal in Major Depressive Disorder (MDD). Although consistency among physician and patient expectations may influence the therapeutic result (Demyttenaere K et al, 2011), patients' perceptions are not always fully captured. Vortioxetine, a multimodal antidepressant, has shown encouraging data in achieving functional recovery, improving both mood and cognitive symptoms (Mahableshwarkar AR et al, 2015). Objectives: The aim of the study was to assess the effectiveness of vortioxetine on mood symptoms, cognitive symptoms and functionality, assessed by patient-rated tools, in MDD outpatients in Greece. Methods: In this non-interventional study, vortioxetine was administered as flexible dosing (5-20 mg/d). Mood symptoms, cognitive symptoms and functioning were assessed by the patient-rated scales PHQ-9, PDQ-D and SDS respectively, at baseline, 1 and 3 months. Repeated measures analysis of variance and t-test were used for the statistical analyses. Results: 336 patients participated in the study. PHQ-9 score ±SD decreased from 16.1±5.3, to 10.0±5.7 and 4.6±4.5, PDQ-D score ±SD decreased from 37.3±16.6 to 23.1±14.8 and 12.0±10.6, SDS Score ±SD decreased from 18.7±5.3 to 12.9±5.9 and to 7.8±6.5, at baseline, 1 and 3 months, respectively. The 3 SDS subscales: work/school life improved from 5.8±2.4 to 4.2±2.2 and 2.6±2.2, social life improved from 6.6±2.0 to 4.5±2.2 and 2.7±2.3 and family life improved from 6.3±2.0 to 4.3±2.1 and 2.6±2.3 -baseline, 1 and 3 months, respectively (p<0.001 for all paired comparisons). Conclusions: MDD patients in Greece treated with vortioxetine significantly improved on mood symptoms, cognitive symptoms and functioning, enriching the already published efficacy data which is mostly based on clinician-rated scales. Conflict of interest: A. Galanopoulos and E. Papalexi are full-time employees in Lundbeck Hellas.